Imago iudicis, štiri podobe iz idejne zgodovine sojenja - Novak, Aleš (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2015)
The article traces the developing image of a judge in Western legal thought. It starts with the famous Montesquieu's characterisation of a judge as "the mouth that pronounces the words of the law". Despite our common intuition (that he was describing a Continental judge), he was, the author argues, in fact offering his best understanding of an English judge. His portrayal has to a large extent corresponded with the self-understanding an English judge of that time (and long afterwards) surely held. Gradually, Montesquieu's image of a judge became synonymous with formalistic approach to judging, triggering a backlash. The German Free Law Movement is perhaps the most influential embodiment of such a reaction. Arguing for the recognition of a creative aspect of judging, they relied on their understanding of a common law judge, which was then still at odds with the official self-image cultivated by English judges. In the next decades, the same disillusion with a mechanistic image of judging prevalent also in the United States gave rise to American Legal Realism. The Realists adopted the Free Law Movement agenda to an important extent, part and parcel with the conviction that judicial creativity is an innate characteristic of a judge's role. It is this conviction that still occupies the centre of all modern theories on judicial decision-making.
Keywords: delitev oblasti; odločanje; pravosodje; sodniki